Viscoelasticity: Mathematical Modeling, Numerical Simulations, and Experimental Work - Ferrás, Luís L.; Afonso, Alexandre M. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue brings together the latest advancements across various facets of viscous and viscoelastic fluid flows. Encompassing a spectrum of contributions, the topics span from innovative numerical methods and sophisticated mathematical modeling to cutting-edge experimental research. In addition to providing insights into the current state of research in these domains, the issue aims to foster a comprehensive understanding of the intricate dynamics and behaviors exhibited by viscous and viscoelastic fluids.